2012
DOI: 10.5210/jur.v5i1.7509
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Infrared Spectroscopy of Ammonia Borane

Abstract: Transmission infrared spectroscopy can potentially offer unique advantages in studying the mechanisms of hydrogen loss from complex hydrides that are being considered for use as hydrogen storage materials. An apparatus that permits infrared spectra to be obtained over a temperature range of 85 to 1200 K and under either an ambient pressure of selected gases or under vacuum has been designed and its performance characterized. While the method is capable of producing high quality spectra at room temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…As explained in the Experimental Section, h-BN layers on clean Ni(111) were obtained by dehydrogenation of the borane-ammonia complex. Recently, it has been demonstrated that this molecule can be fully dehydrogenated to h-BN at high temperature . Our data are comparable to the literature, , where the borazine precursor was used.…”
Section: Resultssupporting
confidence: 89%
“…As explained in the Experimental Section, h-BN layers on clean Ni(111) were obtained by dehydrogenation of the borane-ammonia complex. Recently, it has been demonstrated that this molecule can be fully dehydrogenated to h-BN at high temperature . Our data are comparable to the literature, , where the borazine precursor was used.…”
Section: Resultssupporting
confidence: 89%
“…The band at 3142 cm −1 was assigned to the stretching vibration of the hydroxyl (O-H) group of water molecules and amines (N-H) present in the pores of the zeolites [22]; bands at 1639 cm −1 were attributed to the O-H bending vibration of water molecules [23]. The band at 1400 cm −1 in untreated zeolite may be affected by characteristics peak of NH 4 + and a similar band has been observed for treated zeolites after the ion exchange process [24]. Bands at 1227 and within the range of 1070 to 1150 cm −1 were referred to the external asymmetric stretch and the internal asymmetric stretch of T-O-T, respectively.…”
Section: Zeolite Catalyst Characterizationsmentioning
confidence: 89%
“…Strictly speaking, before accepting an IR spectrum, measured by transmission of IR light through KBr pellet, its validity should be ascertained by other independent methods. Among all publications which deal with IR spectroscopy of AB, some discussion on matrix-initiated spectral variations is found only in those by Taylor and Jash. , Another commonly used technique of recording IR spectra is attenuated total reflection (ATR). However, one must be aware that the spectra obtained by the two techniques are not necessary equal, since the optical setup of ATR gives an information on near-surface level of the sample under consideration, depending on the nature of the sample. , …”
Section: Introductionmentioning
confidence: 99%